The impacts of traditional eastern diet on the community health and environment sustainability - Mohamed Zain, Izzah Nadhirah; Abdul Rahman, Haliza; Ezani, Nur Eliani; Mohd Norowi, Noris (Universiti Sultan Zainal Abidin, 2022)
Traditional Eastern diets are often based on grains, beans, and other healthful foods. It is usually low in red meat and rich in whole grains, vegetables, fruits, and seafood [1]. According to the World Health Organization, a healthy diet includes fruits, vegetables, legumes, nuts, whole grains, meat, fish, eggs, and milk. Each intake varies depending on individual characteristics such as age, gender, lifestyle, and level of physical activity. A healthy diet is essential because it provides a balanced diet to protect against many chronic non-communicable diseases, such as heart disease, diabetes, and cancer [2]. Healthy and sustainable food choices contribute to a series of Sustainable Development Goals, including SDG 2, SDG 3, SDG 11, and SDG 12. These goals are to ensure food security, an improvement in health and well-being, sustainable cities, and communities, and lastly, responsible consumption and production.